The Way They See It: Gender Readings of Filipino Children's Programs on Mainstream Television - Canlas, Data Tolentino (Review of Women's Studies; Vol 20 No 1-2 (2010): Review of Women's Studies Volume XX, Numbers 1-2 (January-December 2010), 2011)
This article explores what gender messages exist in children's television programs in the Philippines. It seeks to discover stereotyped portrayals and roles of the programs' presenters and lead characters through the identification of these personalities' activities and their reactions to situations presented in the programs, as well as the way these personalities are presented.